Existence of Solutions for Impulsive Fractional q-difference Equations with Nonlocal Condition - Vivek, D.; Kanagarajan, K.; Harikrishnan, S. (Journal of Applied Nonlinear Dynamics, 2026)
This paper is devoted to proving the existence of solutions to frac- tional impulsive q-difference equations. An approach based on the Schaefer’s fixed point theorem to prove existence of the solution is presented. There is almost no work on the existence results for im- pulsive fractional q-difference equations. The main aim of this paper is to close this gap.